Cambrian sessile, suspension feeding stem-group ctenophores and evolution of the comb jelly body plan - Zhao, Y; Vinther, J; Parry, LA; Wei, F; Green, E; Pisani, D; Hou, X; Edgecombe, GD; Cong, P (Elsevier, 2019)
The origin of ctenophores (comb jellies) is obscured by their controversial phylogenetic position, with recent phylogenomic analyses resolving either sponges or ctenophores as the sister group of all other animals. Fossil taxa can provide morphological evidence that may elucidate the origins of derived characters and shared ancestries among divergent taxa, providing a means to “break” long branches in phylogenetic trees. Here we describe new fossil material from the early Cambrian Chengjiang Biota, Yunnan Province, China, including the putative cnidarian Xianguangia, the new taxon Daihua sanqiong gen et sp. nov., and Dinomischus venustus, informally referred to as “dinomischids” here. “Dinomischids” possess a basal calyx encircled by 18 tentacles that surround the mouth. The tentacles carry pinnules, each with a row of stiff filamentous structures interpreted as very large compound cilia of a size otherwise only known in ctenophores. Together with the Cambrian tulip animal Siphusauctum and the armored Cambrian scleroctenophores, they exhibit anatomies that trace ctenophores to a sessile, polypoid stem lineage. This body plan resembles the polypoid, tentaculate morphology of cnidarians, including a blind gastric cavity partitioned by mesenteries. We propose that comb rows are derived from tentacles with paired sets of pinnules that each bear a row of compound cilia. The scleroctenophores exhibit paired comb rows, also observed in Siphusauctum, in addition to an organic skeleton, shared as well by Dinomischus, Daihua, and Xianguangia. We formulate a hypothesis in which ctenophores evolved from sessile, polypoid suspension feeders, sharing similarities with cnidarians that suggest either a close relationship between these two phyla, a striking pattern of early convergent evolution, or an ancestral condition for either metazoans or eumetazoans.